Effect of Modified Kimpul Flour Substitution and Glycerol Monostearate Concentration on The Physicochemical and Sensory Properties of Sweet Bread - Siti Nurlaela Setianingsih; Rizky Muliani Dwi Ujianti; Iffah Muflihati; Fafa Nurdyansyah; Mega Novita; Diva Julia Paramita; Shindi Nofitasari; Dola Mareta Anggarini; Abdillah Fathan Generus Annajah (Biology, Medicine, & Natural Product Chemistry, 2025)
Wheat flour is the primary ingredient in sweet bread production, yet its import-dependent supply in countries like Indonesia prompts the need for alternative local ingredients. Kimpul tuber (Xanthosoma sagittifolium), rich in carbohydrates, presents a promising substitute, though its native starch properties are less suitable for baking. This study aimed to evaluate the effect of substituting wheat flour with heat moisture treatment (HMT)-modified kimpul flour and the addition of glycerol monostearate (GMS) on the physicochemical and sensory properties of sweet bread. A factorial completely randomized design was applied using three wheat-to-kimpul flour ratios (3:1, 1:1, and 1:3) and three GMS concentrations (2%, 3%, and 4%). Results showed that higher kimpul flour substitution increased moisture and carbohydrate content but reduced protein and fat levels. Textural properties such as hardness and adhesiveness also increased with kimpul content, but these were mitigated by the addition of GMS, particularly at 3%. The optimal formulation 1:1 wheat-to-kimpul ratio with 3% GMS produced sweet bread with the best overall sensory acceptance. The findings suggest that HMT-modified kimpul flour combined with GMS can serve as a functional and acceptable alternative to wheat flour in bread production. This supports food diversification strategies and promotes the utilization of local tuber-based flours in bakery applications.